Cotton fiber reinforced damping-based composite material and preparation method thereof
By modifying the surface of cotton fiber and hydrogenated nitrile rubber and chemical grafting using isophorone diisocyanate, the problem of insufficient interfacial binding force is solved, the interface performance of the composite material is enhanced, and its application range is expanded.
Patent Information
- Application Number
- CN202510452176.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-11
- Publication Date
- 2025-08-05
AI Technical Summary
The interface bonding force between cotton fiber and hydrogenated nitrile rubber is insufficient, especially in high strength, high temperature or harsh environments, the fibers are easily extracted from the damping matrix and cannot form a whole.
By modifying the surface of cotton fibers and hydrogenated nitrile rubber, hydroxy and carboxy active groups were introduced, and isophorone diisocyanate was used as the coupling layer, and the two were chemically grafted to form molecular bridges to enhance the interface binding force.
It improves the interface bonding performance of cotton fiber reinforced damping matrix composites and broadens its application range in high strength, high temperature or harsh environments.
Smart Images

Figure CN120422531A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of composite material manufacturing, and particularly relates to a cotton fiber reinforced damping-based composite material and a preparation method thereof. Background Art
[0002] Damping, as a viscoelastic material, is a material that can convert mechanical vibration energy into heat energy or other forms of energy dissipation. It is widely used in vibration reduction, noise reduction and other fields.
[0003] Because the introduction of viscoelastic materials reduces the structural stiffness of composite structures to a certain extent, their application areas are limited. Cotton fiber-reinforced damping materials combine the low density, high moisture absorption, and good mechanical properties of cotton fibers with the energy dissipation characteristics of damping materials. They can provide excellent damping performance while maintaining structural stiffness, making them a hot topic in composite material research.
[0004] Since cotton fiber is hydrophilic and rubber is hydrophobic, the interfacial compatibility between the two is poor when they are directly combined. In addition, the surface of hydrogenated nitrile rubber is mainly non-polar hydrocarbon chains and a small amount of polar groups, which is chemically inert as a whole and has poor interfacial bonding ability with cotton fiber. Therefore, improving the interfacial bonding between cotton fiber and rubber matrix has become a key research issue. Commonly used methods are to modify the surface of cotton fiber, such as photoinitiators, enzyme catalysis, chemical coating and plasma treatment. The characteristics of these methods are that they do not fundamentally solve the problem of insufficient interfacial bonding force. After being subjected to force, the fiber is easily pulled out of the damping matrix. Especially under high strength, high temperature or harsh environment, the interfacial bonding force between traditional damping materials and rubber is insufficient, and they cannot form a whole. Summary of the Invention
[0005] In view of this, the present application provides a cotton fiber reinforced damping-based composite material and a preparation method thereof to solve the problem that the interface bonding strength of traditional damping materials in the prior art is insufficient, which makes it easy for fibers to be pulled out of the damping matrix after being subjected to force, especially in high strength, high temperature or harsh environment, where the interface bonding strength between fibers and rubber is insufficient and they cannot form a whole.
[0006] The technical solutions of this application to solve the above technical problems are as follows:
[0007] A method for preparing a cotton fiber reinforced damping-based composite material comprises the following steps:
[0008] S10 cotton fiber surface modification: The cotton fiber was immersed in a sodium hydroxide solution, and then removed from an ultrasonic water bath at a first temperature for a predetermined time, washed and dried to obtain a modified cotton fiber, and sealed for storage;
[0009] S20. Surface modification of hydrogenated nitrile rubber: adding hydrogenated nitrile rubber to a tetrahydrofuran solution to obtain a hydrogenated nitrile solution, wherein the mass ratio of the hydrogenated nitrile rubber to the tetrahydrofuran solution is 1:5 to 1:10;
[0010] adding maleic anhydride and benzoyl peroxide to the hydrogenated nitrile solution, stirring at a second temperature for a second predetermined time; then adding deionized water, heating to a third temperature, stirring for a third predetermined time, adding ethanol solution, precipitating, filtering, washing the surface of the precipitate, drying to obtain a modified hydrogenated nitrile rubber, and sealing and storing for later use;
[0011] S30. The modified cotton fiber and the modified hydrogenated nitrile rubber are respectively prepared into a modified cotton fiber film sheet and a modified hydrogenated nitrile rubber film sheet;
[0012] S40. Take a plurality of the modified cotton fiber film sheets and the modified hydrogenated nitrile rubber film sheets and alternately stack them to form a preform, wherein a layer of isophorone diisocyanate is included between the two adjacent modified cotton fiber film sheets and the modified hydrogenated nitrile rubber film sheets, and the outermost layers of the upper and lower surfaces of the preform are modified hydrogenated nitrile rubber film sheets;
[0013] S50. Place the preform into a press molding die, hot-press for 2 to 5 hours, then take out the die and place it on a workbench to cool, thereby obtaining a modified cotton fiber reinforced damping-based composite material.
[0014] Preferably, in the method for preparing the cotton fiber reinforced damping-based composite material, in step S10, the mass fraction of the sodium hydroxide solution is 1% to 15%.
[0015] Preferably, in the method for preparing the cotton fiber reinforced damping-based composite material, in step S10, the first temperature is 25° C. to 80° C., and the first predetermined time is 1 hour to 3 hours.
[0016] Preferably, in the above-mentioned method for interfacial modification of cotton fiber reinforced damping-based composite materials, in step S20, the mass of the maleic anhydride is 1% to 10% of the mass of the hydrogenated nitrile rubber, and the mass of the benzoyl peroxide is 0.01% to 5% of the mass of the hydrogenated nitrile rubber.
[0017] Preferably, in the method for preparing the cotton fiber reinforced damping-based composite material, in step S20, the second temperature is 50° C. to 100° C., and the second predetermined time is 3 hours to 10 hours.
[0018] Preferably, in the method for preparing the cotton fiber reinforced damping-based composite material, in step S20, the third temperature is 40° C. to 80° C., and the third predetermined time is 1 hour to 4 hours.
[0019] Preferably, in the above-mentioned method for preparing the cotton fiber reinforced damping-based composite material, the thickness of the modified cotton fiber film sheet and the modified hydrogenated nitrile rubber film sheet are both 0.05 mm to 0.3 mm.
[0020] Preferably, in the method for preparing the cotton fiber reinforced damping-based composite material, in step S50, the preform is placed in a forming mold of a press machine with a working temperature of 100° C. to 300° C. and a working pressure of 0.5 MPa to 5 MPa.
[0021] A cotton fiber reinforced damping-based composite material is prepared by adopting the above-mentioned preparation method of the cotton fiber reinforced damping-based composite material.
[0022] The present invention adopts the above technical solution, which has at least the following beneficial effects:
[0023] The invention discloses a cotton fiber reinforced damping-based composite material and a preparation method thereof, the method of improving the interface mechanical properties of the cotton fiber reinforced damping-based composite material by grafting the material surface, cotton fiber and hydrogenated nitrile butadiene rubber (HNBR) are subjected to interface treatment, hydroxyl and carboxyl active groups are introduced on the material surface, and then the hydroxyl on the cotton fiber surface and the carboxyl on the hydrogenated nitrile butadiene rubber surface are connected with isophorone diisocyanate (IPDI) as a coupling layer to form a "molecular bridge", chemical grafting is achieved between rubber and fiber, the interfacial bonding force between molecules is enhanced, the intermolecular interface bonding performance of the fiber reinforced damping film is made better, the two are grafted into a whole, and the interface bonding performance is effectively improved. The deficiency of viscoelastic damping material can be made up, the foundation is laid for the widespread application of cotton fiber reinforced damping-based composite material, and the practical application range of fiber reinforced damping-based composite material is widened, particularly in high strength, high temperature or harsh environment. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 Shown are the molecular structure models of MAH, BPO and IPDI, where Figure 1 (a) is the molecular structure model of MAH; Figure 1 (b) is the molecular structure model of BPO; Figure 1 (c) is the molecular structure model of IPDI.
[0025] Figure 2 The diagram shows the principle of interlayer grafting of HNBR and cotton fibers by IPDI.
[0026] Figure 3 Shown is a schematic diagram of the laying order of cotton fiber and HNBR.
[0027] Figure 4 The EDS images of cotton fibers before and after IPDI treatment are shown. Figure 4 (a) EDS image of cotton fiber before IPDI treatment; Figure 4 (b) EDS image of cotton fiber after being treated with IPDI.
[0028] Figure 5 The EDS diagram of HNBR before and after modification is shown. Figure 5 (a) is the EDS image of HNBR before modification; Figure 5 (b) is the EDS graph of HNBR after modification.
[0029] Figure 6 Shown is the EDS image of modified HNBR after coating with IPDI.
[0030] Figure 7 Shown are the FTIR spectra of HNBR and cotton fibers at different treatment stages.
[0031] Figure 8 Shown is a process flow chart for improving the interface bonding performance between cotton fiber and HNBR molecules. DETAILED DESCRIPTION
[0032] It should be noted that, in the absence of conflict, the embodiments and features of the embodiments of the present invention can be combined with each other. The following will further describe the technical solution of the present invention in conjunction with the drawings of the embodiments of the present invention, and the present invention is not limited to the following specific embodiments.
[0033] See Figures 1 to 8 In one embodiment of the present invention, a method for preparing a cotton fiber reinforced damping-based composite material comprises:
[0034] S10 cotton fiber surface modification: The cotton fiber was immersed in a sodium hydroxide solution, and then removed from an ultrasonic water bath at a first temperature for a predetermined time, washed and dried to obtain a modified cotton fiber, and sealed for storage;
[0035] Furthermore, the mass fraction of the sodium hydroxide solution is 1% to 15%. The sodium hydroxide solution is prepared by using deionized water to prepare a solution with a mass fraction of 1% to 15%. Sodium hydroxide does not destroy the surface structure of the material and can expose more hydroxyl groups on the surface of the cotton fiber, providing active sites for the subsequent grafting reaction.
[0036] Preferably, the first temperature is 25° C. to 80° C., and the first predetermined time is 1 hour to 3 hours. After soaking in an ultrasonic cleaner in a water bath, the cotton fiber is cleaned and dried by washing the surface of the cotton fiber three times with deionized water, and then drying the cleaned cotton fiber in an oven at 40° C. to 80° C. for 0.5 hour to 2 hours to obtain the modified cotton fiber.
[0037] S20. Surface modification of hydrogenated nitrile rubber:
[0038] The hydrogenated nitrile rubber is added to the tetrahydrofuran solution to obtain a hydrogenated nitrile solution, wherein the mass ratio of the hydrogenated nitrile rubber to the tetrahydrofuran solution is 1:5 to 1:10, and the concentration of the tetrahydrofuran solution in the present application is 100%.
[0039] Maleic anhydride and benzoyl peroxide are added to the hydrogenated nitrile solution, and stirred at a second temperature for a second predetermined time; then deionized water is added, and the solution is heated to a third temperature and stirred for a third predetermined time, and then an ethanol solution is added, precipitated, filtered, and the surface of the precipitate is washed. After drying, the modified hydrogenated nitrile rubber is obtained, and the rubber is sealed and stored for later use.
[0040] In this step, the purpose of using maleic anhydride and benzoyl peroxide to treat hydrogenated nitrile rubber is: Benzoyl peroxide (BPO) will decompose under heating conditions to produce free radicals, which can attack the active sites on the hydrogenated nitrile rubber molecular chain. The generated hydrogenated nitrile rubber free radicals can better react with maleic anhydride molecules. The anhydride group of maleic anhydride (MAH) can generate polar carboxyl groups through hydrolysis reaction. The molecular structures of benzoyl peroxide and maleic anhydride are as follows:
[0041]
[0042] In a preferred embodiment, the mass of the maleic anhydride is 1% to 10% of the mass of the hydrogenated nitrile rubber, and the mass of the benzoyl peroxide is 0.01% to 5% of the mass of the hydrogenated nitrile rubber.
[0043] Furthermore, the second temperature is 50° C. to 100° C., and the second predetermined time is 3 hours to 10 hours; the third temperature is 40° C. to 80° C., and the third predetermined time is 1 hour to 4 hours.
[0044] For example, step S20 is specifically as follows: cutting the hydrogenated nitrile rubber into small pieces with scissors, adding the pieces to a tetrahydrofuran solution, wherein the mass ratio of the hydrogenated nitrile rubber to the tetrahydrofuran solution is 1:5 to 1:10, stirring for 4 to 8 hours under sealed conditions at room temperature until the hydrogenated nitrile rubber is completely dissolved to form a uniform hydrogenated nitrile rubber solution for later use; adding 1% to 10% of maleic anhydride by mass of the hydrogenated nitrile rubber and 0.01% to 5% of benzene peroxide by mass of the hydrogenated nitrile rubber to the hydrogenated nitrile rubber solution. to form a mixture, placing the mixture in a drying oven at a temperature of 50° C. to 100° C., stirring in a magnetic stirrer for 3 h to 10 h to obtain a hydrogenated butyronitrile solution after the reaction, and setting aside; pouring a large amount of water into the hydrogenated butyronitrile solution after the reaction, heating to 40° C. to 80° C., stirring in a magnetic stirrer for 1 h to 4 h, and then pouring into an ethanol solution, standing for 30 to 60 minutes to precipitate a precipitate, filtering and washing the surface of the precipitate, and drying to obtain a modified hydrogenated butyronitrile rubber, which is sealed and stored for later use.
[0045] S30. The modified cotton fiber and the modified hydrogenated nitrile rubber are respectively made into a modified cotton fiber film sheet and a modified hydrogenated nitrile rubber film sheet; in practical applications, the modified cotton fiber film sheet can be directly modified with sheet-shaped cotton fibers, such as cotton fiber woven fabrics.
[0046] S40. Take a plurality of the modified cotton fiber film sheets and the modified hydrogenated nitrile rubber film sheets and alternately stack them to form a preform, wherein a layer of isophorone diisocyanate is included between the two adjacent modified cotton fiber film sheets and the modified hydrogenated nitrile rubber film sheets, and the outermost layers of the upper and lower surfaces of the preform are modified hydrogenated nitrile rubber film sheets;
[0047] Furthermore, the thickness of the modified cotton fiber film sheet and the modified hydrogenated nitrile rubber film sheet are both 0.05 mm to 0.3 mm.
[0048] The purpose of using isophorone diisocyanate (IPDI) as the intermediate medium is that the polar -NCO groups at both ends of the isophorone diisocyanate molecule can react chemically with the hydroxyl groups on the cotton fiber and the carboxyl groups on the rubber, respectively, to effectively connect the two materials and achieve chemical grafting. The molecular structure of isophorone diisocyanate is as follows:
[0049]
[0050] Based on the special molecular structure of isophorone diisocyanate, IPDI is used as an intermediate medium to connect the interface between cotton fiber and rubber. After the surface treatment of the fiber and rubber, the material surface contains -OH groups and -COOH groups respectively. Both polar groups can react with the -NCO polar groups at both ends of IPDI, forming a chemical bond connection between the composite material bonding interface.
[0051] S50. Place the preform into a press mold, hot-press for 2 to 5 hours, then remove the mold and cool it on a workbench to obtain a modified cotton fiber reinforced damping-based composite material. Furthermore, the press mold has an operating temperature of 100° C. to 300° C. and an operating pressure of 0.5 MPa to 5 MPa.
[0052] The processed modified hydrogenated nitrile rubber film sheets and modified cotton fiber film sheets with a thickness of 0.05 mm to 0.3 mm are cut into several squares of the same size, with one more modified hydrogenated nitrile rubber film sheet than the modified cotton fiber film sheet; a layer of isophorone diisocyanate with a thickness of 0.025 mm is applied on the surface of the cut modified hydrogenated nitrile rubber film sheets and modified cotton fiber film sheets respectively, and after evenly applying, they are laid out in a designed layering order to form a preform.
[0053] The preform is placed in a mold, and the molding working temperature of the press is set to 100°C to 300°C and the working pressure is set to 0.5MPa to 5MPa. After the temperature reaches the preset temperature, the mold is placed in a hot press for 2 hours to 5 hours, and then the mold is taken out and placed on a workbench to cool. After cooling to room temperature, the demolding cloth is opened to obtain a cotton fiber reinforced hydrogenated nitrile rubber composite material.
[0054] The present invention is different from the traditional viscoelastic damping brush coating method for making damping composite material structures, and proposes a new method for improving the interface bonding performance of materials. The traditional brush coating method for making damping composite material structures is simply to dissolve the damping and then brush it on the carbon fiber, which affects the rigidity of the composite material structure and cannot be widely used. The present invention is to firstly graft the surface of hydrogenated nitrile rubber with maleic anhydride and benzoyl peroxide solution to generate functionalized rubber with carboxyl groups; secondly, isophorone diisocyanate is coated on the surface of the modified fiber and rubber film, and the polar -NCO functional groups at both ends are used to connect the hydroxyl groups on the fiber and the carboxyl groups on the rubber to form a "molecular bridge", realizing chemical grafting between the rubber and the fiber, so that the intermolecular interface bonding performance of the fiber-reinforced damping film is better, making up for the shortcomings of viscoelastic damping materials, and broadening the practical application range of fiber-reinforced damping-based composite materials, especially high strength, high temperature or harsh environments.
[0055] In another specific embodiment of the present invention, a cotton fiber reinforced damping-based composite material is prepared by the above-mentioned preparation method of the cotton fiber reinforced damping-based composite material.
[0056] It is worth noting that the process temperature and process time involved in the above-mentioned embodiments are the temperature or time adopted in the experimental process. Those skilled in the art can make reasonable adjustments within the error range based on the process temperature and process time provided by the present invention, which should be included in the protection scope of the present invention.
[0057] The following is a detailed description of the technical solutions and effects of the present invention through specific experimental examples.
[0058] 1. Materials and sources
[0059] The materials and reagents in the examples of the present invention are commercially available and can be used without further purification.
[0060] 2. Test methods
[0061] (1) Energy dispersive X-ray spectroscopy (EDS) was used to analyze the surface elemental composition of the material at each processing stage with an accelerating voltage of 10 kV.
[0062] (2) Fourier transform infrared spectrometer (FTIR) was used to analyze the changes in the surface functional groups of cotton fibers before and after surface treatment, before and after modification with hydrogenated nitrile rubber, and after surface treatment and modification with hydrogenated nitrile rubber to determine whether chemical grafting was achieved between the rubber and fiber layers. The experiment was conducted in ATR mode with a scanning range of 400-4000 cm -1 , spectral resolution is 4cm -1 , and plot the obtained data into a graph.
[0063] 3. Examples
[0064] (1) Surface modification of cotton fiber and HNBR
[0065] The cotton fiber used in this implementation process is a cotton fiber woven cloth. 1L of a 5% by mass sodium hydroxide solution is prepared. The sodium hydroxide does not destroy the surface structure of the material and can expose more hydroxyl groups on the surface of the cotton fiber, providing active sites for the subsequent grafting reaction. The prepared sodium hydroxide solution is poured into an SCQ-1020B ultrasonic cleaner, and the cleaned cotton fiber is immersed in the prepared sodium hydroxide solution. The water bath temperature is set to 60°C. After ultrasonic immersion for 2 hours, the cotton fiber is removed, rinsed with deionized water, and then placed in an oven for drying to obtain a modified cotton fiber woven cloth, which is then sealed and stored for later use.
[0066] Cut the hydrogenated nitrile rubber into small pieces with scissors, add them to a tetrahydrofuran solution with a mass ratio of hydrogenated nitrile rubber to tetrahydrofuran solution of 1:7, stir evenly for 8 hours under sealed conditions at room temperature until the hydrogenated nitrile rubber is completely dissolved, add 5% of maleic anhydride by mass of the hydrogenated nitrile rubber and 1% of benzoyl peroxide by mass of the hydrogenated nitrile rubber to the solution, stir at 75°C for 4 hours, pour a large amount of water into the solution, stir at 60°C for 2 hours, and then pour into an ethanol solution to precipitate the hydrogenated nitrile rubber, filter and wash the surface of the precipitate, and obtain a hydrogenated nitrile rubber film after drying, which is sealed and stored for later use.
[0067] (2) Preparation of composite materials
[0068] The treated modified hydrogenated nitrile rubber film sheet with a thickness of 0.1 mm and the modified cotton fiber woven cloth were cut into 10 cm × 10 cm squares, the modified cotton fiber woven cloth was cut into 5 pieces, and the modified hydrogenated nitrile rubber film sheet was cut into 6 pieces; a layer of isophorone diisocyanate with a thickness of 0.025 mm was applied on the surface of the cut fiber and rubber film, and after evenly applied, it was laid in the designed layering order to form a preform, such as Figure 3 shown.
[0069] The preform was placed in a 10 cm × 10 cm mold, and the press molding working temperature was set to 130 ° C and the working pressure was set to 3 MPa. After the temperature reached 130 ° C, the mold was placed in hot pressing for 2 hours, and then the mold was taken out and placed on the workbench to cool. After cooling to room temperature, the demolding cloth was opened to obtain a cotton fiber reinforced hydrogenated nitrile rubber composite material sample.
[0070] 4. Micro testing
[0071] (1) Microscopic principle analysis:
[0072] like Figure 1 The molecular chains of MAH, BPO and IPDI are shown. Figure 2 The principle of IPDI interlayer grafting HNBR / cotton fiber is shown in the figure. After the surface treatment of the fiber and resin, -OH and -COOH groups are introduced, which react with the -NCO polar groups at both ends of IPDI to form a chemical bond between the materials. The chemical reaction is shown in the following formula:
[0073] R-NCO+R'-OH→R-OCONH-R',
[0074] R-NCO+R'-COOH→R-CONH-R'+CO2.
[0075] (2) Energy dispersive X-ray spectrometer EDS micrograph:
[0076] Figure 4 (a) and Figure 4 (b) shows the EDS spectrum of cotton fiber before and after grafting treatment. After grafting, N element appears on the surface. Through infrared spectroscopy analysis, it can be determined that chemical connection bonds are formed on the cotton fiber under the action of IPDI.
[0077] Figure 5 (a) and 5(b) are the EDS spectra of HNBR before and after surface modification. O element appears on the surface after treatment. Figure 6 This is the spectrum of the treated HNBR surface coated with IPDI. Through infrared spectroscopy analysis, it can be determined that HNBR forms chemical bonds under the action of IPDI.
[0078] (3) FTIR spectrum analysis:
[0079] The above invention principle and implementation process can be verified through microscopic experiments, such as Figure 7 As shown in the spectrum, the specific verification analysis is as follows:
[0080] FTIR was used to characterize the chemical groups on the HNBR surface at each treatment stage to analyze whether new chemical bonds were generated. Figure 7 (a) is the infrared spectra of HNBR before and after modification with maleic anhydride and benzoyl peroxide; Figure 7 (b) Infrared spectra of cotton fiber and HNBR film after IPDI was introduced. Figure 7 (a) In the spectrum curve a, 1782 cm -1 and 1865cm -1 The peak at 1700 cm is the C=O stretching vibration peak in the anhydride group, which shows that compared with curve b, it can be inferred that maleic anhydride is grafted onto the HNBR surface under the action of benzoyl peroxide; -1 The C=O stretching vibration peak in the carboxyl group, 3315 cm -1 The peak at (b) is the stretching vibration peak of OH in the carboxyl group. Compared with curve b, it can be inferred that the carboxyl group exists on the surface of the HNBR hydrolyzed after modification with maleic anhydride and benzoyl peroxide. Figure 7 (b) In the spectrum curves c and d, 1544 cm -1 and 1583cm -1 The NH bending vibration peaks of the carbamate group and the amide group are 1658 cm -1 and 1700cm -1 The C=O stretching vibration peaks of the carbamate group and the amide group are 3465 cm -1 and 3338cm -1 The NH stretching vibration peaks of the carbamate group and the amide group are 1222 cm -1 The changes in these characteristic peaks indicate that IPDI reacted chemically with cotton fiber and modified HNBR to form new chemical groups, namely, carbamate group and amide group.
[0081] The present invention proposes a complete set of flow charts for improving the interfacial mechanical properties of cotton fiber reinforced hydrogenated nitrile rubber composite materials using isophorone diisocyanate. Figure 8 As shown, the process was used to successfully produce cotton fiber hydrogenated nitrile rubber composite specimens, which have excellent interface bonding properties.
[0082] Obviously, the above embodiments of the present invention are merely examples for the purpose of clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. A person skilled in the art would be able to make other variations or modifications based on the above description. It is not necessary and impossible to enumerate all embodiments here. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention shall be included within the scope of protection of the present invention.
Claims
1. A method for preparing a cotton fiber reinforced damping-based composite material, characterized in that: The following steps are involved: S10. Cotton fiber surface modification: The cotton fiber is immersed in a sodium hydroxide solution, and then removed from an ultrasonic water bath at a first temperature for a predetermined time, washed, dried, and the modified cotton fiber is sealed and stored for later use; S20. Hydrogenated nitrile rubber surface modification: adding hydrogenated nitrile rubber to a tetrahydrofuran solution to obtain a hydrogenated nitrile solution, wherein the mass ratio of the hydrogenated nitrile rubber to the tetrahydrofuran solution is 1:5 to 1:10; adding maleic anhydride and benzoyl peroxide to the hydrogenated nitrile solution, stirring at a second temperature for a second predetermined time; then adding deionized water, heating to a third temperature, stirring for a third predetermined time, adding ethanol solution, precipitating, filtering, washing the surface of the precipitate, drying to obtain a modified hydrogenated nitrile rubber, and sealing and storing for later use; S30. The modified cotton fiber and the modified hydrogenated nitrile rubber are respectively prepared into a modified cotton fiber film sheet and a modified hydrogenated nitrile rubber film sheet; S40. If the dry modified cotton fiber film sheet and the modified hydrogenated nitrile rubber film sheet are alternately stacked to form a preform, the modified cotton fiber film sheet and the modified hydrogenated nitrile rubber film sheet between the two adjacent sheets include a layer of isophorone diisocyanate, and the outermost layers of the upper and lower surfaces of the preform are modified hydrogenated nitrile rubber film sheets; S50. Place the preform into a press molding die, hot-press for 2 to 5 hours, then take out the die and place it on a workbench to cool, thereby obtaining a modified cotton fiber reinforced damping-based composite material.
2. The method for preparing the cotton fiber reinforced damping-based composite material according to claim 1, wherein: In step S10, the mass fraction of the sodium hydroxide solution is 1% to 15%.
3. The method for preparing the cotton fiber reinforced damping-based composite material according to claim 1, wherein: In step S10, the first temperature is 25°C to 80°C, and the first predetermined time is 1 hour to 3 hours.
4. The method for preparing the cotton fiber reinforced damping-based composite material according to claim 1, wherein: In step S20, the mass of the maleic anhydride is 1% to 10% of the mass of the hydrogenated nitrile rubber, and the mass of the benzoyl peroxide is 0.01% to 5% of the mass of the hydrogenated nitrile rubber.
5. The method for preparing the cotton fiber reinforced damping-based composite material according to claim 1, wherein: In step S20, the second temperature is 50°C to 100°C, and the second predetermined time is 3 hours to 10 hours.
6. The method for preparing the cotton fiber reinforced damping-based composite material according to claim 1, wherein: In step S20, the third temperature is 40°C to 80°C, and the third predetermined time is 1 hour to 4 hours.
7. The method for preparing the cotton fiber reinforced damping-based composite material according to claim 1, wherein: The thickness of the modified cotton fiber film sheet and the modified hydrogenated nitrile rubber film sheet are both 0.05 mm to 0.3 mm.
8. The method for preparing the cotton fiber reinforced damping-based composite material according to claim 1, wherein: In step S50 , the preform is placed in a forming mold of a press machine with a working temperature of 100° C. to 300° C. and a working pressure of 0.5 MPa to 5 MPa.
9. A cotton fiber reinforced damping-based composite material, characterized in that: The composite material is prepared by the preparation method of the cotton fiber reinforced damping-based composite material according to any one of claims 1 to 8.